North Flinders Reef (Coral Sea, Australia) Porites sp. corals as a candidate Global boundary Stratotype Section and Point for the Anthropocene series. (April 2023) - Zinke, Jens; Cantin, Neal E; DeLong, Kristine L; Palmer, Kylie; Boom, Arnoud; Hajdas, Irka; Duprey, Nicolas; Martínez-García, Alfredo; Rose, Neil L; Roberts, Sarah L; Yang, Handong; Roberts, Lucy R; et al.
Corals are unique in the suite of proposed Anthropocene Global Boundary Stratotype Section and Point (GSSP) archives, as living organisms that produce aragonite exoskeletons preserved in the geological record that contain highly accurate and precise (<±1 year) internal chronologies. The GSSP candidate site North Flinders Reef in the Coral Sea (Australia) is an offshore oceanic reef, and therefore less vulnerable to local human influences than those closer to the coast. Here, we present geochemical records from two Porites sp. corals sampled at an annual to pluri-annual (i.e. 3–5 years) resolution that shows clear global and regional human impacts. Atmospheric nuclear bomb testing by-products ( 14 C, 239+240 Pu) show a clear increase in the Flinders Reef corals coincident with well-dated nuclear testing operations. By contrast, the radionuclides 241 Am and 137 Cs are present at low or undetectable levels, as are spheroidal carbonaceous fly-ash particles. Coral δ 13 C shows centennial variability likely influenced by growth effects in the 18th century and with a progression to lower values starting in 1880 CE and accelerating post-1970 CE. The latter may be related to the Suess effect resulting from 13 C-depleted fossil fuel burning. Coral δ 15 N decreased between 1710 and 1954 CE with a reversal post-1954 CE. Coral temperature proxies indicate prominent centennial variability with equally warm conditions in the 18th and end of 20th century. However, the exact mechanisms responsible for the mid-20th century changes in these parameters need to be scrutinised in further detail. Plain Language summary: This work proposes a candidate natural archive for the official marker of the Anthropocene that geologists will use to mark this important interval in time. Our candidate is a live coral from North Flinders Reef in the Coral Sea (Australia), located 150 km east of the Great Barrier Reef, a location that is remote from direct local human influences. Corals are a unique archive of tropical ocean change because they incorporate the geochemical signature from seawater into their limestone skeleton during their long life-spans. Here we investigated a number of geochemical markers in yearly growth layers of the corals to define several markers for the Anthropocene based on changes in temperature, water chemistry, chemicals from pollution and fertilisers, radioactive products from nuclear bomb testing, and by-products from burning fossil fuels. We have detected clear human influences in several of these markers.